Generation z’s critical attitude toward digital misinformation among tiktok - Nanda Ayu Refinita; Ayu Maya Damayanti; Adi Nur Aziz (Institute Of computer Science (IOCS), 2026)
The rapid development of digital technology has transformed social media into a primary source of information, particularly for Generation Z. Among various platforms, TikTok facilitates rapid information dissemination but simultaneously increases users' exposure to hoaxes and misinformation. Although previous studies have widely examined digital literacy and misinformation, limited research has specifically explored how Generation Z develops critical attitudes toward hoaxes on TikTok through everyday information verification practices. Addressing this gap, this study analyzes Generation Z's critical attitudes toward digital hoaxes on TikTok, identifies the verification strategies they employ, and examines the factors influencing their ability to evaluate information. This study adopted a qualitative descriptive approach involving five Generation Z informants aged 18–25 years who actively use TikTok. Data were collected through in-depth interviews, observation, and documentation and analyzed using the Miles, Huberman, and Saldaña interactive model. The findings indicate that most informants demonstrate critical attitudes by verifying information before believing or sharing it. Their verification practices include checking the credibility of information sources, comparing content across multiple media platforms, examining user discussions in the comment section, and confirming information through official institutions or trusted news outlets. Critical attitudes are influenced by digital literacy, educational background, social environment, prior social media experience, and TikTok's algorithmic characteristics. This study contributes to the literature by providing an in-depth understanding of the interaction between digital literacy, platform-specific characteristics, and critical information evaluation among Generation Z. The findings also offer practical insights for developing digital literacy programs aimed at strengthening resilience against online misinformation.